Image and text presentation forms in destination marketing: An eye-tracking analysis and a laboratory experiment - Yang, Wei; Chen, Qiuxia; Huang, Xiaoting; Xie, Jiaxin; Xie, Mei; Shi, Jiamin (Frontiers in Psychology, 2022)
Tourism destination marketing has been an heated focus in tourism academia, but there is a lack of research on different graphic presentation forms in tourism advertisements. To bridge the gap in the tourism literature, this study aims at studying the impact of the image and text presentation forms of the scenic spot's name in tourism advertisements on tourists' visit intention to the tourist destination city by combining the theory of constructivism in cognitive psychology, SOR model, and affective-cognitive model to conduct a 2×2 between-group experiment. The study found that when the text part contains the scenic spot's name, the tourism advertisement has a significant impact on tourists' perceived advertising effectiveness, destination affective image, and visit intention.  The results of eye tracking analysis also showed that fixation points are primarily distributed in the text part. Furthermore, this study explored the chain mediating mechanism of perceived advertising effectiveness and destination affective image and discovered that the impact of the text presentation form on the visit intention can be realized through the mediating effect of perceived advertising effectiveness and destination affective image. This study puts forward some suggestions for the tourism advertising and destination marketing of scenic spots with high-familiarity of destination cities with low-familiarity and improving the image of tourist destination cities.